The Effect of Herb-acupunctures of Bojoongiggi-tang (Buzhongyiqi-tang), Ginseng Radix, and Astragali Radix on Immune Responses in Rats - Kim, Jung-Hun; Park, Hi-Joon; Lee, Hyang-Sook; Lee, Hye-Jung (Korean Pharmacopuncture Institute, 2000)
Objectives : To investigate the effects of herb-acupunctures of Qi tonification herbs or formula on the rat immune depression induced by an anticancer drug, methotrexate (MTX) Methods: Animals were divided into 5 groups; Normal control group was not given any treatment. Immune depression was induced by oral administration of 1mg/kg MTX b.i.d for 4 days in Control, Sample I, II, and III groups. We treated on CV 4 (Guanyuan) with saline, Bojoongiggi-tang (Buzhongyiqi-tang), Ginseng Radix and Astragali Radix herb-acupunctures in Control, Sample I, II, and Ill groups, respectively. In both blood and spleen, the assessment of CD4+ T-cell count, CD8+ T-cell count, CD4/CD8 T-cell ratio was performed. Results: Here we show that 3 herb- acupuncture groups have an influence, to some extent, on CD4+ and CD8+ T-cell counts and CD4/CD8 T-cell ratio in both blood and spleen. Astragali Radix herb-acupuncture, in particular, was found to have significantly increased CD4+ T-cell count in blood and CD4/CD8 T-cell ratio in blood and spleen. Conclusions: The results of this study suggest that herb-acupunctures of Bojoongiggi-tang (Buzhongyiqi-tang), Ginseng Radix and Astragali Radix may have an influence over rat immune depression induced by MTX.